Development of High Dietary Fiber Cereal Bar as Emergency Food Product and The Chemical-Microbiological Properties and Nutritional Content - Ani Radiati; Sumarto Sumarto; Fahmi Hafid; Emma Kamelia; Lia Nurcahyani; Dini Mariani; Siti Badriah; Tjahja Muhandri (Amerta Nutrition)
Background: Dietary fiber is essential for maintaining digestive health, especially during emergencies with limited food availability.